Water-soluble nanomaterials self-assembly for improving the stability of natural food preservatives: A Review - I Dewa Agung Panji Dwipayana (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
Food spoilage is still a global problem, contributing to foodborne illness, economic losses, and environmental burdens associated with food waste. Conventional chemical preservatives, while effective, face increasing regulatory restrictions and consumer concern regarding potential health risks, driving demand for safer and more natural alternatives. Natural preservatives such as essential oils, phenolic compounds, and antimicrobial peptides offer broad-spectrum antimicrobial and antioxidant activities but are limited by poor water solubility, volatility, degradation during processing, and inconsistent efficacy in complex food matrices. This narrative review examines recent advances in water-soluble self-assembled nanomaterials as stabilization and delivery systems for natural food preservatives. Emphasis is placed on supramolecular self-assembly principles, key non-covalent interactions in aqueous environments, common nanostructures including cyclodextrin inclusion complexes, polymer micelles, nanoemulsions, hydrogels, and vesicles, as well as assembly and characterization methods relevant to food applications. The review further discusses major food spoilage mechanisms and bacterial pathogens, highlighting synergistic effects achieved by combining nanomaterials with natural preservatives to enhance antimicrobial efficacy, prolong shelf life, and reduce sensory impacts. While these systems demonstrate significant promise for clean-label food preservation, challenges related to scalability, cost, sensory optimization, safety, migration, and regulatory acceptance remain. Addressing these issues through green synthesis, mechanistic studies, and robust safety assessments will be essential to support the responsible translation of self-assembled nanomaterials into practical and sustainable food preservation strategies.